Reversible window with low-e glass - Mohd Ali, Mohamad Zulhilmi Haziq (2022)
In this era, green building has become sensation worldwide. Regarding to the environmental sustainability, all parties has taken these issues seriously. Malaysia is one of the countries that involve in Sustainable Development Goals agenda. To promote sustainable development, Malaysian government issued the Green Technology Policy in July 2009. This report is aligned to the sustainable objectives of the policy by implementing idea of generating a product that able to improves the sustainability of building. Window had been chosen to be the element of the innovation. Windows design have significant impact on the sustainability of a building. This element plays a crucial role in determining the energy performance of the building. This report will analysis and find a solution to create a product that able to achieve the sustainability perspective and the goal of green campus. Various study had been made such as the goals of Sustainable Goal Development, green campus concept and type of current windows used for student’s accommodation in UiTM Seri Iskandar. The purpose of this report is to make an improvement for windows in terms of design, materials and type of glass panel.